Polycyclic polyprenylated acylphloroglucinols from the bark of mesua ferrea and their anti-diabetic activity / Nurulfazlina Edayah Rasol - Rasol, Nurulfazlina Edayah (2014)
The ethyl acetate extract of the bark of Mesua ferrea from Clusiaceae family was studied for its chemical constituent’s together with a-amylase and a-glucosidase inhibitory activities for potential anti-diabetic properties. The phytochemistry investigation resulted in the isolation of seven new polycyclic polyprenylated acylphloroglucinols of type B(I). Various chromatographic techniques were used in the isolation process. For fractionation, VLC, TLC and MPLC were employed.Purification of the compounds was accomplished using repeated HPLC technique due to very close retention time. Structures of the isolated compounds were established by means of spectroscopic methods which includes ID-NMR (*H and *^C), 2D-NMR (COSY, HSQC, HMBC, NOESY and TOCSY), UV, IR and LCMS. The compounds were named mesuaferroic acid A, mesuaferroic acid B, mesuaferroic acid C, mesuaferroic acid D, mesuaferroic acid E, mesuaferroic acid F and mesuaferroic acid G. Polycyclic polyprenylated acylphloroglucinols have never been reported in Mesua species before. All the extracts and isolated compounds were subjected to a-amylase and a-glucosidase inhibitory assays for potential anti-diabetic properties. The results obtained from both assays indicate that the ethyl acetate extract has potential for antidiabetic with moderate a-amylase and strong a-glucosidase inhibitory activity. The hexane extract showed strong inhibition properties for both assays and methanol showed strong a-amylase but did not show a-glucosidase inhibitory activity. Of the seven pure compounds, mesuaferroic acid D, mesuaferroic acid E and mesuaferroic acid F may be regarded as having moderate anti-diabetic property with ICso values of 345.87 ng/ml, 260.97 (xg/ml and 349.50 ^g/ml, respectively in the a-glucosidase inhibition assay as compared to 1-deoxynojirimycin standard IC50 values of 102.82 Hg/ml.